IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM MENCIPTAKAN PEMBELAJARAN YANG BERKESADARAN BERMAKNA DAN MENGGEMBIRAKAN PADA MATERI MENGGAMBAR PERSPEKTIF DI SMAN 1 PADANG : Penelitian kualitatif - Yuke Trey Silfani; Yofita Sandra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning perspective drawing requires not only mastery of spatial concepts and drawing techniques but also students' ability to connect theoretical concepts with real-world practice. Therefore, a learning approach that promotes mindful, meaningful, and joyful learning experiences is needed. This study aimed to: (1) analyze the implementation of the Deep Learning Approach in perspective drawing instruction at SMAN 1 Padang; and (2) analyze how art teachers implemented the Deep Learning Approach through mindful, meaningful, and joyful learning in teaching perspective drawing. This research employed a qualitative approach using a case study design. The research participants consisted of an art teacher, the vice principal for curriculum, and students of Class XI F1. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through source and technique triangulation. The findings revealed that the Deep Learning Approach was implemented through three stages: planning, implementation, and assessment. During the learning process, students developed their understanding of perspective concepts by observing and analyzing real objects, applied these concepts in perspective drawing practice, and reflected on both the learning process and their artwork based on teacher feedback. The implementation of mindful, meaningful, and joyful learning principles fostered a more active, contextual, and student-centered learning environment, which enhanced students' motivation, creativity, self-confidence, and understanding of perspective drawing.